ХАНДГАЙТЫН МОЛИБДЕНЫ ОРДЫН ХҮДЭРЖИЛТ, ГАРАЛ ҮҮСЛИЙН ТААМАГЛАЛ - А. БАТБААТАР; П.БАТЧУЛУУН (Geological Issues, 2023)
In the Zhed ore region distributed small and medium leucocratic granitic massifs with rare metal mineralization. These granites are composite of sericite and muscovite, although new formed and feldspars are altered by pellite. The main ore mineral molybdenite occurs as disseminated and stockwork type of mineralization. Here intended to present a brief information of origin of the Khandgait molybdenum deposit which is associated with middle Jurassic Zelter intrusive complex that distributed in the Zed rare metal ore region. The Khandgait disseminated molybdenite deposit essentially hosted in the Mid Jurassic Zelter intrusive complex which is related to formed the Zelter continental rifting zone. Disseminated molybdenite is hosted by 3-phase a fine grained granite of Middle Jurassic Zelter intrusive complex which is formed in a continental rift zone and lower Cambrian stockwork type of molybdenite mineralization is hosted by lower-middle Zed formation sedimentary rocks.